2020
DOI: 10.1152/japplphysiol.00856.2019
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of central activation of the diaphragm: a mechanism of weaning failure

Abstract: During a T-tube trial following disconnection of mechanical ventilation, patients failing the trial do not develop contractile diaphragmatic fatigue despite increases in inspiratory pressure output. Studies in volunteers, patients, and animals raise the possibility of spinal and supraspinal reflex mechanisms that inhibit central-neural output under loaded conditions. We hypothesized that diaphragmatic recruitment is submaximal at the end of a failed weaning trial despite concurrent respiratory distress. Tidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 111 publications
(232 reference statements)
0
14
0
Order By: Relevance
“…In a physiologic study, Laghi and co-workers demonstrated that patients who failed a weaning trial did not develop contractile fatigue of the diaphragm (consistent with muscle injury), potentially leading to subsequent unsuccessful weaning attempts or unsuccessful liberation from the ventilator 25 . Moreover, these investigators were able to show that diaphragmatic recruitment at the end of a failed weaning trial, estimated by the electrical activity of the diaphragm, was half of the maximum, corresponding to reflex inhibition of the diaphragm with at the same time redistribution of motoneuron output to rib cage and accessory muscles, a potential mechanism for the prevention of diaphragmatic contractile fatigue 26 . Accordingly, patients categorized as difficult to wean, failing up to three SBT before successful discontinuation of mechanical ventilation, showed no increase in ICU‒ or hospital mortality compared to patients successfully extubated on the first attempt 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In a physiologic study, Laghi and co-workers demonstrated that patients who failed a weaning trial did not develop contractile fatigue of the diaphragm (consistent with muscle injury), potentially leading to subsequent unsuccessful weaning attempts or unsuccessful liberation from the ventilator 25 . Moreover, these investigators were able to show that diaphragmatic recruitment at the end of a failed weaning trial, estimated by the electrical activity of the diaphragm, was half of the maximum, corresponding to reflex inhibition of the diaphragm with at the same time redistribution of motoneuron output to rib cage and accessory muscles, a potential mechanism for the prevention of diaphragmatic contractile fatigue 26 . Accordingly, patients categorized as difficult to wean, failing up to three SBT before successful discontinuation of mechanical ventilation, showed no increase in ICU‒ or hospital mortality compared to patients successfully extubated on the first attempt 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment of expiratory muscles under mechanical ventilation is wellknown and may limit the increase in EELV (51) through a physiological feedback mechanism involving proprioceptive influences and vagal pathways (52,53). Recruitment of expiratory muscles generates an increase in abdominal pressure moving the diaphragm to a more cranial position at end-expiration, thereby counteracting the effect of PEEP and improving neuromechanical coupling by placing the diaphragm at a more optimal length for tension generation (51,54,55). It is unknown why only a subset of subjects recruited their expiratory muscles.…”
Section: Effect Of Increased Peep On Diaphragm Contractile Efficiencymentioning
confidence: 99%
“…For more extensive discussion, we refer to recent articles (3,10). Second, the relationship between diaphragm weakness and ICU outcomes, including difficult weaning and ICU mortality, has been observed to various degrees in observational studies (2,(29)(30)(31)(32)(33)(34)(35), but whether diaphragm weakness is a causal contributor to poor ICU outcomes or a merely a marker for disease severity remains to be established (36). A causal relationship seems plausible, as the diaphragm is the main muscle of inspiration and improving diaphragm strength led to improved weaning outcome in selected patients (37).…”
Section: Diaphragm Effort Diaphragm Weakness and Icu Outcomesmentioning
confidence: 99%